Interlinking major markets to explore electric car uptake. (September 2020) - Gómez Vilchez, Jonatan J.; Jochem, Patrick; Fichtner, Wolf
Abstract: The purpose of this research is to investigate policy synergies and market interdependencies in the field of alternative powertrain technologies. The methodology is based on a simulation model grounded on system dynamics, a method that focuses on the structure (particularly feedback processes) and behavior over time of complex systems. The impacts of four policy measures on the uptake of electric cars in six countries (China, France, Germany, India, Japan and the United States), each segmented in five consumer groups, are explored. We observe that the additive impact of individual policies is lower than the impact of a corresponding policy package and that the impact of a policy package is greater if pursued by countries jointly. The implications of these findings are that the uptake of electric powertrains may depend not only on the combined impact of country-specific policy measures but also on the joint effect of policies in key electric car markets. The originality of this research arises from the endogenization of the electric car battery price evolution by explicitly modeling policy packages in six major car markets and interlinking them. Highlights: System dynamics model captures feedback processes affecting electric car uptake. Four policy measures investigated, individually and in combination. Policies in China, France, Germany, India, Japan and the US examined. Policy analysis results in identification of synergetic effects. Public policy coordination supports faster electric car deployment.